Geoethics : ethical challenges and case studies in earth sciences - Wyss, Max, 1939-; Peppoloni, Silvia (©2015, 2015)
'The time for a first book on Geoethics has come. The faster, greedier pace of society and globalization demands it. The comfortable life of scholars in the ivory tower is coming to a rude awakening. People demand understandable information on geo-hazards, judges condemn scientist and engineers for lack of communication, indigenous people rise in anger accusing experts of misleading them, attempts to avoid transparency in developments still exist, the helplessness of technology to deal with nuclear waste becomes more evident every day and nature exposes shortcuts in constructing critical facilities with her own awesome force. Less dramatic, but damaging the credibility of the scientific community is the rising number of cases of plagiarism, made easy by the electronic world of communication. In addition, the community of geoscientists needs to become aware of subtle ways in which our work can be useless for or even misleading the public'--
Includes bibliographical references and index.
Keywords: Geology -- Research -- Moral and ethical aspects; Geophysics -- Research -- Moral and ethical aspects; Research -- Moral and ethical aspects -- Case studies